2017
DOI: 10.17957/ijab/15.0254
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of Cotton Germplasm for Cotton Leaf Curl Disease Caused by Viral Strains

Abstract: To cite this paper: Slaeem, H., A.A. Khan, M.T. Azhar and M.S. Nawaz-ul-Rehman, 2017. Molecular screening of cotton germplasm for cotton leaf curl disease caused by viral strains. Int. J. Agric. AbstractCotton crop is infected by single stranded DNA viruses (Family, Geminiviridae) in Pakistan. Due to changing global climate, which favors the whitefly (insect vector) growth and reproduction, the spread of cotton leaf curl disease is increasing at an alarming rate. Various approaches are being used to diagnose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…During the decomposition of organic matter, release of nutrients and organic compounds increases growth and yield traits (Hendrix et al, 1994). Similar results were reported by Iqbal et al (2010). Shah et al (2022) reported similar results regarding spike length.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the decomposition of organic matter, release of nutrients and organic compounds increases growth and yield traits (Hendrix et al, 1994). Similar results were reported by Iqbal et al (2010). Shah et al (2022) reported similar results regarding spike length.…”
Section: Discussionsupporting
confidence: 90%
“…Different investigators have found that turgor decreases due to water stress conditions, but membrane stability does not get affected under water stress conditions (Jatoi et al, 2011). Similar results were reported by (Iqbal et al, 2010) for various wheat cultivars under water stress levels. Relative water contents have been reported as one of the key signs of water stress in plant leaves and is closely associated with cell volume, thus it may more accurately reflects the balance between availability of water to leaves and transpiration rate (Merah, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…We observed a wide range of responses among 100 elite cultivars/varieties during the initial screening against CLCuD (Javed et al, 2017). Based on germplasm screening and the available literature (Batool et al, 2021; Javed et al, 2017; Saleem et al, 2017), a highly tolerant genotype MNH‐886 and the highly susceptible genotype S‐12 were chosen to develop their segregating plant populations. The phenotypic performance for CLCuD severity of both parents (MNH‐886 and S‐12) and their segregating F2 and F3 populations were further observed for two seasons (Table 1).…”
Section: Resultsmentioning
confidence: 99%